The Lexicon on Natural Knowledge of Umpasa in Batak Toba - Sitorus, Nurhayati; Lubis, Tasnim (Tradition and Modernity of Humanity, 2023)
Umpasa is a kind of rhyme used by the Batak Toba tribe in traditional events. Every umpasa conveyed undoubtedly has meaning, and it becomes a guideline for the Batak Toba. This study aims to find the scientific lexicon contained in umpasa, and the meaning of the umpasa. The data is taken from Jambar Hata Dongan Tu Ulaon Adat. Data collection is done through observation and note-taking techniques. After the data is collected, the data is analyzed using Miles and Huberman's analysis, which consists of three stages: the data reduction stage, the data presentation stage, and the data conclusion/verification stage. The result of this study was the lexicon found in umpasa Batak Toba consists of natural knowledge of flora and fauna. Furthermore, the umpasa in Batak Toba functions as a prayer or hope. So, in the example, the Batak Toba characterizes human traits or characteristics from parts of flora and fauna.